1968
DOI: 10.1021/ar50003a002
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-rotation in the hydrolysis of phosphate esters

Abstract: Abstract. The hydrolysis of a phosphate, phosphonate or phosphinate ester generaUy takes place either through a trigonal bipyramidal hydroxyphosphorane as intermediate (with expansion of the coordination number of phosphorus from four to five) or (at least for phosphates) through a moaomeric metaphosphate as intermediate (with contraction of the coordination number of phosphorus from four to three). These processes parai.lel the principal mechanisms for the hydrolysis of carboxylic esters, which require either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
438
0
5

Year Published

1979
1979
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(459 citation statements)
references
References 83 publications
(34 reference statements)
16
438
0
5
Order By: Relevance
“…This locking might be rationalized in terms of the ability of Vi to form a coordination complex with nucleophilic residues at the active site. The tetrahedral vanadate ion has the capacity either to exchange ligands or to accept a fifth ligand (as in crystalline metavanadates) to form a trigonal bipyramidal complex (13), which resembles the transition state for phosphoryl transfer (2,24,25). Although there is no evidence of a five-coordinate V1 species in free solution (13,(26)(27)(28), such a complex might be stabilized at the myosin active site.…”
Section: Resultsmentioning
confidence: 99%
“…This locking might be rationalized in terms of the ability of Vi to form a coordination complex with nucleophilic residues at the active site. The tetrahedral vanadate ion has the capacity either to exchange ligands or to accept a fifth ligand (as in crystalline metavanadates) to form a trigonal bipyramidal complex (13), which resembles the transition state for phosphoryl transfer (2,24,25). Although there is no evidence of a five-coordinate V1 species in free solution (13,(26)(27)(28), such a complex might be stabilized at the myosin active site.…”
Section: Resultsmentioning
confidence: 99%
“…Since the nucleophile attacks from an axial position, the leaving group has to depart from an axial position also, which is facilitated by the pseudo-rotation. Finally, while this pseudorotation mechanism is quite rare and specialized (Westheimer, 1968), semi-empirical studies of phosphate monoester hydrolysis at different levels of phosphate and nucleophile protonation have demonstrated that not only is the non-inline associative mechanism with pseudo-rotation a reasonable reaction pathway, but there are certain conditions under which it can even be the lowest energy pathway (Wilkie & Gani, 1996). The barrier for the pseudo-rotation step is so low, however, that it is difficult to observe it either computationally or experimentally.…”
Section: Non-inline Mechanisms With Pseudo-rotationmentioning
confidence: 99%
“…99 Trigonal bipyramidal species are stabilised to the greatest extent possible if the most electronegative atom(s) occupy the apical sites. This arrangement of the substituents 30 results in the HOM O being as low in energy as is possible.…”
Section: Oxaphosphetane Structure and Cycloreversion Mechanismmentioning
confidence: 99%
“…The OPA formed by the cycloaddition step is postulated to have the oxygen in the apical position, in accordance with Westheimer's rule on apical entry 15 and departure for a phosphorus-centred trigonal bipyramid. 99 This OPA, (which could be any one of a number of pseudorotamers with apical oxygen) is proposed to undergo rapid pseudorotation to a less stable pseudorotamer with ring carbon-3 in an apical position, and the ring oxygen in an equatorial site. This 20 pseudorotamer undergoes [2+2] cycloreversion to alkene and phosphine oxide.…”
mentioning
confidence: 99%